Analisis Persepsi Publik Terhadap Jurusan Kearsipan : di Indonesia - Arumsari, Ghufita; Meisya, Nayla Shintia; Setiawati, Anggi Rizki; Mukhbita, Alya; Mashia, Tamara Annisa; Putri, Azqia Nadiya; Setiono, Naila Khalisa; Nurizzki, Ali Manan (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This research analyze public perceptions of Archives majors in higher education through a qualitative approach with a content analysis method. Data were obtained from the responses of ten Quora platform user accounts related to views on job prospects, specialization, and relevance of the Archiving major. The results showed that public perception of this major tends to be neutral to positive. The parameters “tone” and “competent” obtained the highest mean scores, each at 2.3, reflecting that the majority of responses were delivered in a supportive manner and by competent parties. However, the parameters “narrative” and “image” remained at an average score of 2, indicating that the public perception of the Archives major is not yet fully strong. The results show that the archives major should be seen as a relevant and strategic field in the digital age. These results underscore the importance of effective communication strategies, improved information literacy, and collaboration between students, professionals, and educational institutions.